Validity of sentinel node biopsy in early oral and oropharyngeal carcinoma. Issue 10 (October 2018) - Riese, C.G.U.; Karstadt, J.-A.; Schramm, A.; Güleryüz, S.; Dressel, G.; Lorenz, K.J.; Klemenz, B.; Sailer, A.; Seitz, S.; Wilde, F.
Abstract: Purpose: This study investigates the possibility and sensibility of using sentinel node biopsy (SNB) during surgery for oropharyngeal carcinomas with clinically and radiographically unremarkable cervical lymph nodes. Materials and methods: A total of 36 patients who were treated for early oral and oropharyngeal carcinoma and unremarkable cervical lymph nodes were included in this study. After lymphoscintigraphy for detecting sentinel lymph nodes (SLN), the SLN were excised first. Thereafter elective neck dissection was performed. Histopathological and immunochemical examinations were used to examine the SLN and all other lymph nodes. Results: The preoperative SLN detection rate was 97.2% (35 of 36). SLN in level V were detected in four patients (11.1%). Metastases were found in 33.3% of the patients (12 of 36). All metastases were in the marked SLN. No skip metastases could be detected. A specificity of 100% and a sensitivity of 94.4% were identified for the SNB. Conclusion: The study confirms that SNB is a precise diagnostic procedure for assessing the nodal status of cervical lymph nodes. Further studies are needed to determine whether SNB without elective neck dissection for clinically and radiologically unremarkable cervical lymph nodes can become a reliable course of treatment for carcinomas of the head and neck region.